Effect of Red Fruit Oil Soap (Pandanus Conoideus Lam.) as Wound Cleansing on Wound Healing and the Number of Bacterial Colonies among Grade II Diabetic Ulcer Patients at Griya Wound Care Clinic Kudus, Indonesia - Hevny Kartika Dewi; Mardiyono Mardiyono; Diyah Fatmasari; Sudirman Sudirman; Djenta Saha (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Diabetic ulcer is an open wound on the skin layer to the dermis due to hyperglycemia and neuropathy. This condition often causes infection and becomes an inhibitor in the wound healing process. Red fruit oil soap can be used as an alternative cleansing to reduce the number of bacterial colonies and accelerate the wound healing process.Aims: This present study aimed to observe the effect of red fruit oil soap in the cleansing process to reduce the number of bacterial colonies and the wound healing process in grade II Diabetic ulcer patientsMethods: This is a quasi-experimental study with the pre-test post-test non-equivalent control group design. Wound cleansing in the intervention group used 0.9% NaCl solution and red fruit oil soap with a pH of 5.74, while the wound cleansing in the control group used 0.9% NaCl solution. Bacterial colonies were assessed and the type of bacteria was observed by the swab method. The wound healing was assessed with Bates-Jensen Wound Assessment Tool (BWAT) instrument for 14 days with observations every 3 days. Analysis test used Mann Whitney and Repeated Measure ANOVA.Results: There was no difference in the mean of the number of bacterial colonies between the wounds that were cleansed with 0.9% NaCl solution and red fruit oil soap and the wounds which were cleansed by using 0.9% NaCl solution (p> 0.05). The mean of the number of colonies in the intervention group until the 14th day reduced by 3.14x106 and in the control group was reduced h 1.40x106. There was a significant decrease in the wound healing scores in each group, in each assessment for 14 days.Conclusion: This study found that the wound cleansing using red fruit oil soap and 0.9% NaCl solution could reduce the number of bacterial colonies on the wound surface and accelerate the wound healing process among patients with grade II diabetic ulcer.